Analysing City-Regions in a Vietnamese Context: An Overview of Concepts, Definitions and Development Policy Implications - Son, Le Minh (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 36 No 2, 2020)
In recent years, Vietnam has made forward-looking steps in endorsing and promoting City-region development with appropriate vision and leadership. However, there appears to be rather limited literature on the city-region as well as a gap between how the ‘city-region’ is understood conceptually and the relevant policies being advocated. To have a more thorough consideration of whether such advocacy is appropriate, a more thorough comprehension of concepts, definitions and implications is necessary. This paper aims to contribute to this literature gap, firstly by demonstrating how city-regions are functional economic areas which can be empirically studied. Secondly, by analyzing the Vietnamese legal framework using the Hanoi Capital Region and the Ho Chi Minh City Region as case studies, this paper presents arguments that City-region development in Vietnam is highly normative and politically guided. Some major identified challenges come from poor data collection and lack of formal recognition. Urgent changes in perspective, as well as data collection practice, are needed to enable a unified approach to city-regions, which is of interest to both academics and policy-makers.